Sintesis Karbon Aktif Dari Batang Jagung(Zea mays L.) dengan Metoda Dehidrasi Asam Untuk Aplikasi Elektroda Superkapasitor - Tetra, Olly Norita; Syukri, Syukri; Santoni, Adlis; Deswati, Deswati; Fajarandi, Nabiel; Emriadi, Emriadi (Jurnal Fisika Unand, 2024)
Activated carbon from corn stalks (Zea mays L.) has been successfully synthesized by the dehydration method and used as a supercapacitor electrode. Corn stalk powder was dehydrated with 1 MH2SO4 and activated with 5 M NaOH at a carbon and activator mass ratio of 1:4 with a heating temperature of 800°C and an N2 gas heating rate of 10°C/minute for 1 hour. SEM characterization results show that heterogeneous pores have formed on the surface of corn stalk-activated carbon. EDX results showed a carbon percentage of 54.82%; this data is supported by FTIR results, which show several functional groups containing C and O atoms on the surface of activated carbon. Based on desorption adsorption isotherm analysis, the activated carbon shows H4 type with a specific surface area of 117.973m2/g, average pore diameter of 1.730 nm and total pore volume of 0.1021 cm3/g. Measurement of the electrochemical properties of corn stalk activated carbon with a three-electrode system and 3 M KOH electrolyte showed a specific capacitance value of 133.9 F/g, power density 225.2 W/kg and energy density 0.863 Wh/kg. The synthesis of activated carbon through the dehydration method offers advantages in terms of simplicity in preparation, low cost, shorter synthesis time and being environmentally friendly.